IDENTIFIKASI BAHAYA KESELAMATAN DAN KESEHATAN KERJA (K3) DI INDUSTRI TAHU DESA WIRAGUNAN - Salsabila Purnamasari; Nugrahani, Nur 'Aini Azhari; Jenita Berliana (Biro Akademik, Penelitian dan Pengabdian kepada Masyarakat, Universitas Anak Bangsa, 2023)
Sukoharjo is a fairly large MSME industrial center in Indonesia, one of which is the tofu industry which dominates Wirogunan Village. In tofu industry, there are many hazards that can cause various diseases, accidents and injuries such as tripping, slipping, skin irritation (contact dermatitis), musculoskeletal disorders or complaints, etc. Therefore, it is important to know what sources of danger are known in the industry so that risk assessments can then be carried out and recommendations for hazard control can be made. The aim of this research is to identify the dangers that exist in the tofu industry. Hazard identification uses the JSA technique, which is carried out with a Walk Through Survey through observations and interviews with workers, business owners and head of business community. The data obtained will later be entered into the JSA table, so that the hazards that have the highest risk value will be found. These high-risk hazards will later become a priority for providing hazard control or risk management, which will be continued in the next research.